Analysis of minerals and heavy metal content in drinking water, mineral water and tap water by inductive couple plasma mass spectroscopy (ICP-MS) - Mohd Hamzah, Siti Salmiah Azira; Abdullah, Shakila (Penerbit UTHM, 2020)
Malaysian was estimated water intake about 210 liters per day. Drinking water can be obtained from three different sources such as from bottled drinking water, bottled mineral water and tap water. However, these resources likely to be contaminated by the present of the minerals and heavy metal. This is due to industrial activities, types of soils and pollution that occur among the resources. In order to determine the safety level water consumption, the level of minerals and heavy metal from these resources need to be analysed. The level of mineral contents was analysed by using atomic absorption spectroscopy while the level of heavy metal was measured using inductively coupled plasma mass spectroscopy. This paper presents a comparison level of minerals and heavy metals between drinking water (DW), mineral water (MW) and tap water (TW). The maximum average value of cadmium (Cd-111) concentration among the various type of heavy metal was found 121.16 µg L-1 and was presented from TW UTHM. The minimum average value of arsenic (as-75) concentration among the various type of heavy metal was found 0.06 µg L-1 and was presented in DW Dasani. While, the maximum average value of calcium (Ca+) concentration among the various type of mineral contents was found 55.21 mg L-1 and was presented in MW Spritzer. The minimum average value of arsenic (as-75) concentration among the various type of heavy metal was found 0.03 mg L-1 and was presented in DW Dasani. Results showed that all parameters complied with the maximum acceptable value set by DW Quality Standards, Malaysia except for heavy metal parameter.